EST12 regulates Myc expression and enhances anti-mycobacterial inflammatory response via RACK1-JNK-AP1-Myc immune pathway - Wu, Jian; Luo, Feng-Ling; Xie, Yan; Xiong, Huan; Gao, Yadong; Liu, Guanghui; Zhang, Xiao-Lian (Frontiers in Immunology, 2022)
c-Myc (Myc) is a well-known transcription factor that regulates many essential cellular processes. Myc has been implicated in regulating anti-mycobacterial responses. However, its precise mechanism in modulating mycobacterial immunity remains elusive. Here, we found that a secreted Rv1579c (early secreted target with molecular weight 12 kDa, named EST12) protein, encoded by virulent Mycobacterium tuberculosis (M.tb) H37Rv region of deletion (RD)3, induces early expression and late degradation of Myc protein. Interestingly, EST12-induced Myc was further processed by K48 ubiquitin proteasome degradation in E3 ubiquitin ligase FBW7 dependent manner. EST12 protein activates JNK-AP1-Myc signaling pathway, promotes Myc binding to the promoters of IL-6, TNF-α and iNOS, then induces the expression of pro-inflammatory cytokines (IL-6 and TNF-α)/inducible nitric oxide synthase (iNOS)/nitric oxide (NO) to increase mycobacterial clearance in a RACK1 dependent manner, and these effects are impaired by both Myc and JNK inhibitors. Macrophages infected with EST12-deficiency strain (H37RvΔEST12) displayed less production of iNOS, IL-6 and TNF-α. In conclusion, EST12 regulates Myc expression and enhances anti-mycobacterial inflammatory response via RACK1-JNK-AP1-Myc immune pathway. Our finding provides new insights into M.tb-induced immunity through Myc.